Kegiatan Bermain sebagai Terapi bagi Anak-Anak Penyintas Gempa - Indira, Lydia; Nasution, Sri Mulyani; Churnawan, Rizky Purnomo Adji; Indriani, Erry; Andriani, Astri Dwi; Faraitody T., Dody (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
The earthquake that occurred in Cianjur in November 2022 had an impact on all aspects. As a result of the accompanying team's observations and interviews with the children and those closest to them, it was found that the earthquake had an impact on the children's psychological condition. Among other things, they lose the fun and enjoyment of playing with their peers. They experience anxiety and fear and lack self-confidence. Childhood is a golden period in a series of developmental stages. During this period, almost all children's potential experiences rapid growth. This period is important because during this period various physical and psychological aspects develop. Considering this, in community service activities, one of the activities carried out is providing intervention for earthquake survivor children in the form of play therapy as a form of social support so that children can escape psychological trauma and return to age-appropriate developmental stages, such as being able to feel the fun of playing with his friends and exploring. After the intervention was carried out and re-observed, there were visible changes in the behavior shown by the children while playing. Those who were initially quiet, unhappy, and always wanted to be near their mother became active, laughed, and no longer worried after participating in play therapy activities.